The Effect of Concomitant Immunotherapy and Stereotactic Radiotherapy, and of Location on Survival in Patients With Brain Metastases From Melanoma - Chiel B. Nijboer; Djura Piersma; Angelique E. J. Sijben; Besim Hoti; Matthijs van der Meulen (Cancer Medicine)
ABSTRACT Background Melanoma is one of the most common causes of brain metastases (BM). Despite recent therapeutic advances, survival in patients with brain metastases from melanoma (MBM) is dismal. In this study, we analyse the effect of concomitant treatment with stereotactic radiotherapy (SRT) and immunotherapy on survival, and of the location of BM on survival. Methods All patients with MBM diagnosed in Medisch Spectrum Twente, between 2011 and 2023 were included. Patient, radiological, and treatment variables were retrospectively collected. The primary outcome was overall survival (OS) and the secondary outcome was intracranial progression‐free survival (IPFS). The effect of combination treatment (IRT), location, and other known prognostic factors on outcome measures was analysed using univariate and multivariate Cox regression. Location groups were divided into only supratentorial, only infratentorial, and both infra‐ and supratentorial BM. Results 92 patients with MBM were included. The mean age was 64 years with standard deviation (SD) 12, median OS [interquartile range (IQR)] was 9.8 months [4.0–31.0] in the total population. No difference in OS was found between different treatment regimens (n = 56). Patients having both infra‐ and supratentorial BM showed a significantly reduced OS compared to having only supratentorial BM in multivariate analysis (Hazard Ratio (HR): 2.81; 95% Confidence Interval (CI):1.37–5.74; p < 0.01). IRT had a significantly positive effect on IPFS in univariate analysis (HR: 0.32; 95% CI: 0.13–0.77; p = 0.01). Conclusion Concomitant treatment of immunotherapy and SRT is associated with a prolonged IPFS compared to immunotherapy only. Having both infra‐ and supratentorial BM is an independent prognostic factor for a shorter OS.